A Phylogenetic Classification Of Luyia Language Varieties - Marlo, Michael; Grollemund, Rebecca; Nguyen, Thanh; Platner, Erik; Pribe, Sarah; Thein, Alexa (My University, 2022)
This paper presents the results of a comparative study of the Luyia cluster of Bantu languages spoken in western Kenya and eastern Uganda. We propose a new classification of Luyia and neighboring languages using phylogenetic methods. Our study is based on a 200-item wordlist of basic vocabulary, representing 33 language varieties from the Luyia cluster and its closest neighbors, including Ganda, Gwere, and Soga to the west, and Gusii and Kuria to the south. Our results are broadly consistent with past classifications by Mould (1976, 1981) and Williams (1973), but refine our understanding of the relatedness of the target languages by employing more extensive data from more languages within the Luyia cluster and others in the region.
Keywords: Luiya; Bantu language; phylogenetic methods